Post-Surface Processing and Virtual Simulation Analysis of Ball-Punch Test on CP-Ti Material - Ananda Mohan Vemula; G. Chandra Mohan Reddy; M. Manzoor Hussain; Atul Kumar; Naresh Kumar; Haiter Lenin Allasi (Advances in Materials Science and Engineering)
The titanium alloy is one of the prime materials for many engineering applications. It has been recommended for the components in automotive engines, power sector, biomedical industries, and more applications. It is due to the unique properties of the material with good strength and corrosion resistance. However, it is very challenging to handle Ti-based materials in manufacturing sectors without damaging the metallurgical quality. Thus, an attempt made to study the deformability of the CP-Ti material through ball–punch test to represent the stress, strain, and formability limit during mechanical loading and plastic deformation. The experiments are conducted following the ASTM E643 standards to study the material behavior. The maximum cupping reached to a height of 8.69 mm and got teared at the peak of doom. The separation has induced grain detachment due to tensile loading. The same condition is used to simulate with PAM STAMP™ software and 8.48 mm is the maximum cupping height achieved. The different is 0.21 mm. The results are interesting with similar observations and found acceptable to study the deformation.